The Role Of The Agency For Women's Empowerment, Child Protection, Population Control, And Family Planning In Accelerating The Reduction Of Stunting In Seluma Regency - Wulandari, Selfia; Handayani , Tuti; Yusuarsono, Yusuarsono (Journal of Multidisciplinary Research, 2025)
This study aims to determine the role of the women's empowerment, population control, and family planning agencies in accelerating the reduction of stunting in Seluma Regency. The method used in this study is descriptive qualitative. The research information consists of five (5) people, comprising two (2) key informants and three (3) main informants. Data collection methods included observation, interviews, and documentation. Based on the research results and discussion using Soerjono Soekanto's (2001:242) role theory regarding role theory: (1) Active Role: The number of educational and training programs organized by agencies each year in an effort to reduce stunting, the presence of agencies in cross-sector coordination forums on stunting reduction at the regional level, the number of female cadres or volunteers trained by agencies on the issue of stunting prevention, the number of reports and follow-ups on cases of children and women experiencing violence or neglect that have the potential to increase the risk of stunting. (2) Participatory Role: Institutional involvement in development planning meetings (musrenbang) to include issues of women's and children's empowerment in stunting reduction strategies, Number of women's groups or women's community organizations facilitated by institutions to play a role in stunting programs, Level of community participation in activities facilitated by institutions related to stunting prevention, number of forums or cross-sector coordination activities involving institutions. (3) Passive Role: Involvement in policy formulation for accelerating stunting reduction, cross-sector coordination in accelerating stunting reduction, advocacy/public awareness campaigns in accelerating stunting reduction.